Farmer and Fisher Empowerment Model Based On Local Institutions and Agroecosystem to Increase Competitiveness and Income - Amanah, Siti; Farmayanti, Narni (Journal of Rural Indonesia [JORI], 2014)
Small-scale farming and fisheries business are highly dependent on socio-agroecosystem condition, quality and performance of their products. This research aimed at formulating alternative empowerment model of farmer and fisher community. The research used research for development approach with multimethods, including rapid assessment, observation, interview, focused group discussion, action research, and multistakeholders dialogue. Farmer and fisher representatives of six villages from different types of agroecosystem and related informants were involved in the research.Â  Action research was conducted in Muara and Benteng Villages. Research results showed that quality of the products positively correlated to income of farming business. Community awareness and motivation to improve their socio-economics and environment, technical skills and extension services are key factors of successful empowerment. Â© 2014 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: community empowerment, small-scale farmers and fishers, agroecosystem, local institution, extension services, competitivenessÂ